The Incentive Model in Supply Chain with Trade Credit and Default Risk. (2nd May 2019) - Cheng, Hong; Su, Yingsheng; Yan, Jinjiang; Wang, Xianyu; Li, Mingyang
Abstract : Trade credit is widely used for its advantages. However, trade credit also brings default risk to the manufacturer due to the uncertain demand. And moral hazard may aggravate the default risk. The purpose of this paper is to investigate the role of moral hazard in trade credit and explore incentive contract under uncertain demand and asymmetric information. We consider a two-echelon supply chain consisting of a risk-neutral retailer ordering a single product from a risk-neutral manufacturer. Market demand is stochastic and is influenced by retailer's sales effort which is his private information. Incentive theory is used to develop the principal-agent model and get the incentive contract from the manufacturer's perspective. Results show that the retailer will reduce his effort level to get more profit and the manufacturer's profit will be reduced, in the case of asymmetric information. Facing this result, the manufacturer will reduce the order quantity in incentive contract to lessen his losses. Numerical examples are provided to illustrate all these theoretical results and to draw managerial insights.